Relative position of bladder neck to pubic symphysis on cystogram is a strong and reproducible predictor of early urinary continence recovery following radical prostatectomy. Issue 2 (May 2021) - Rossanese, Marta; Caloggero, Simona; Alario, Giuseppe; Mucciardi, Giuseppe; Novara, Giacomo; Giannarini, Gianluca; Ficarra, Vincenzo
Objectives: To assess whether bladder neck angle and position on cystogram predict early urinary continence in patients scheduled for early catheter removal after radical prostatectomy (RP). Methods: A total of 103 patients undergoing open or robot-assisted RP by one expert surgeon between January and December 2019 were retrospectively analyzed. A cystogram was performed on postoperative day 3 or 4 to evaluate anastomotic leakage, and, if none or minimal, the catheter was removed. Urinary continence was evaluated with a validated questionnaire at 1 week, 1 month, and 3 months after RP. Four investigators of different experience assigned bladder neck angle and relative position of bladder neck to pubic symphysis on archived cystogram images. Association between these two parameters and urinary continence rates at different follow-up times was assessed with logistic regression analysis adjusting for patient and tumor characteristics, and surgical technique. Interobserver agreement in assigning the two parameters was measured with k statistic. Results: Catheter was removed immediately after cystogram in 101 (98%) patients. On multivariable analysis, only relative position of bladder neck to pubic symphysis was an independent predictor of 1-week (odds ratio [OR] 30. 95% confidence intervals [CIs] 6-138, p < 0.001), 1-month (OR 11. 95%CIs 3.8-32, p < 0.001), and 3-month (OR 19. 95%CIs 3.6-98, p < 0.001) urinary continence. Interobserver agreement for bladder neck and relative position of bladder neck to pubic symphysis was fair to moderate, and substantial to almost perfect, respectively. Conclusions: Relative position of bladder neck to pubic symphysis on cystogram is a strong and reproducible predictor of early urinary continence after RP.